EFEKTIVITAS PENEGAKAN HUKUM TERHADAP PELAKSANAAN JUAL BELI TANAH DI KOTA PALOPO - Devi, Sari Ratna (Al-Amwal : Journal of Islamic Economic Law, 2019)
The effectivenes of the implementation of buying and selling land in palopo I stillineffective because there are still many people who are still buying and selling landwith a deed under the hand , it can be said that the community has not obeyed the law and some have not influeced it community towards the implementation of the sale and purchase of land in the city palopo